Time Trends and Sex Differences in the Invasive Treatment of Infrainguinal Intermittent Claudication in Sweden During 2009 – 2022 : Results From the Swedish Vascular Registry (Swedvasc) - Gunnarsson, Thordur S.; Bergman, Stefan; Pärsson, Håkan; Gottsäter, Anders; Lindgren, Hans (European Journal of Vascular and Endovascular Surgery, 2025)
Objective: This study aimed to report changes in the annual incidence of invasive treatment, changes in invasive treatment modalities, and sex differences in patients treated for intermittent claudication (IC) due to infrainguinal lesions in Sweden between 2009 and 2022. Methods: Data were collected from the Swedish Vascular Registry (Swedvasc), including all registrations of invasive treatment for infrainguinal IC in Sweden between 2009 and 2022. Results: The annual incidence of invasive treatments showed no statistically significant change between 2009 and 2022 (p = .21). The proportion of open surgery decreased from 38.1% in 2009 to 23.4% in 2022 (p < .001). Endovascular and hybrid interventions increased from 56.9% to 69.7% (p < .001) and from 4.8% to 7.0% (p < .001), respectively, between 2009 and 2022 according to time trend analysis. The decrease in open surgery was due to a reduction in bypass surgery from 18.8% in 2009 to 4.0% in 2022 (p < .001). The proportion of common femoral artery thrombo-endarterectomy remained unchanged (p = .24). During the study period, 42.7% of invasive treatments were performed in women. Open surgery was more frequently performed in men than women (32.5% vs. 24.0%; p < .001). However, endovascular intervention was statistically significantly more frequently performed in women than men (70.7% vs. 61.6%; p < .001). Conclusion: The annual incidence of invasive treatment for infrainguinal IC in Sweden was unchanged between 2009 and 2022. The proportion of endovascular interventions increased and accounted for 70% of invasive treatments in 2022, whereas bypass surgery decreased by 79%. Women were more often treated with endovascular intervention than men.
Keywords: Endovascular; Infrainguinal; Intermittent claudication; Peripheral arterial disease; Swedvasc; Vascular surgery